2016
DOI: 10.15761/jts.1000132
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression response to ascorbic acid in mice implanted with sarcoma S180 cells

Abstract: In recent years, increasing numbers of studies demonstrated that high-dose ascorbate, which can be achieved by intravenous infusion, has cytotoxic effects on cancer cells in vitro and in vivo. There are many hypotheses of anti-cancer mechanisms of high dose ascorbate including a pro-oxidative mechanism, inhibition of angiogenesis and inflammation, enhancement of the anticancer effect of chemotherapy and reduction of chemotherapy-induced side effects. In addition, in recent years there were studies showing that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
2
1
Order By: Relevance
“…Some people are advised by their doctors or dietitian to take dietary supplements especially if they have certain medical conditions such as pregnancy or those who have a restricted dietary intake. Many people also take vitamins and supplements while they are being treated for cancer; others take them to prevent cancer.Cancer patients are increasingly turning to supplements to strengthen their immune systems and ease nausea from chemotherapy [15].Until now, the role of vitamin supplements in preventing breast cancer remains unclear.Contradictory data regard beneficial versus unwanted potentiating carcinogenic effect of vitamin A. Epidemiological studies have suggested an inverse correlation between cancer development and dietary consumption of vitamin A.Our results indicated that vitamin A administration before and after the injection of the EAC cells increased, the BW and TC, these results are in disagreement with a study who suggested that the pharmacological concentrations of vitamin A decrease the incidence of chemically induced experimental tumors [16]. Also other studies reported that natural and synthetic retinoid have been demonstrated to inhibit the growth and the development of different types of tumors, including skin, breast, oral cavity, lung, hepatic, gastrointestinal, prostatic, and bladder cancers [17][18].…”
Section: Discussion:-contrasting
confidence: 98%
See 1 more Smart Citation
“…Some people are advised by their doctors or dietitian to take dietary supplements especially if they have certain medical conditions such as pregnancy or those who have a restricted dietary intake. Many people also take vitamins and supplements while they are being treated for cancer; others take them to prevent cancer.Cancer patients are increasingly turning to supplements to strengthen their immune systems and ease nausea from chemotherapy [15].Until now, the role of vitamin supplements in preventing breast cancer remains unclear.Contradictory data regard beneficial versus unwanted potentiating carcinogenic effect of vitamin A. Epidemiological studies have suggested an inverse correlation between cancer development and dietary consumption of vitamin A.Our results indicated that vitamin A administration before and after the injection of the EAC cells increased, the BW and TC, these results are in disagreement with a study who suggested that the pharmacological concentrations of vitamin A decrease the incidence of chemically induced experimental tumors [16]. Also other studies reported that natural and synthetic retinoid have been demonstrated to inhibit the growth and the development of different types of tumors, including skin, breast, oral cavity, lung, hepatic, gastrointestinal, prostatic, and bladder cancers [17][18].…”
Section: Discussion:-contrasting
confidence: 98%
“…These results are in agreement with [15]who reported that P16 and P53have important roles in the inhibition of cell proliferation via cell cycle arrest and apoptosis. They are mutated in many tumor cell types [16].Human telomerase reverse transcriptase TERT, which regulates telomere length and can promote tumor development, increases the anti-apoptotic capacity of cells and enhance repair. It is thought to aid tumor cell growth and allow tumor cells to become immortal, so that TERT expression is considered a potential target for anticancer therapy.In our study, expression levels of TERTwereelevated in tumor tissue for treated group with vitamin A before inculcated with solid tumor in comparison with non-treated group.VEGV is known as vascular endothelial growth factor (formation of new blood vessels) in this study the expression level of this gene found to be high in O+T+O group, most tumors show higher levels of VEGF, higher levels mean low chance of survival.…”
Section: Discussion:-mentioning
confidence: 99%
“…Recent investigations have shown that ascorbate therapy has a significant effect on the expression of several genes relevant to the development or inhibition of cancer. In particular, the reduced expression of tumor-promoting genes, such as HIF, and the increased expression of tumor-suppressor genes, such as p53, support the notion that vitamin C can act as a potential agent for the suppression of tumor development [53].…”
Section: The Antioxidant Pathwaymentioning
confidence: 66%